Peran Keluarga Dalam Meningkatkan Minat Belajar Anak Di Wilayah Bagek Longgek - Ningsih, Dewi Puspita; Apriawan, Andika (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study are to determine the role of the family in raising children's interest in learning and to determine the inhibiting factors of family role in increasing children's interest in learning at school age. the research method used descriptive qualitative. The location of this research is in Bagek Longgek region with 1 year research time. The subjects of this study was parents who has children that have children in school-age and research objects about parents role in increasing children's learning interest. the instrument of data collection is human instrument, the data analysis technique uses data collection, data reductions, data presentation, and data verification. the results of this study, the role of the family in increasing interest in learning by always looking for the results of their children's study so that they know the children's development, reward and punishment, giving award in form of praise, giving attention, provide the study facilities needed by children, doing an assist both in learning and doing tasks. inhibiting factors increase children's interest because parents can't guide their children study well, lack of attention from the family of results that they got, nor rewards not either punishment. the environment base on high- population area